2020
DOI: 10.1140/epjd/e2020-10084-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of Aharanov–Bohm (AB) and magnetic fields with screened Kratzer potential

Abstract: In this study, the Schrodinger equation (SE) with screened Kratzer potential (SKP) in the presence of external magnetic and AB-flux fields is investigated using the factorization method.The eigenvalue and eigenfunction for the system are obtained in closed form. It is found that the present of the magnetic field partially removes the degeneracy when the screening parameter of the potential was small   0.005   but the addition of the AB field removed the degeneracy faster and better. The magnetization and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 70 publications
4
55
0
Order By: Relevance
“…2 i,j increases with increasing and respectively. The behaviour of the thermal properties in the present study are in accordance with those reported in refs 68 , 71 , 72 . Table 1 is the numerical values for spin symmetry energies for , , and .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2 i,j increases with increasing and respectively. The behaviour of the thermal properties in the present study are in accordance with those reported in refs 68 , 71 , 72 . Table 1 is the numerical values for spin symmetry energies for , , and .…”
Section: Discussionsupporting
confidence: 93%
“…Ikhdair 67 calculated a rotational and vibrational energies of diatomic molecules in Klein–Gordon equation using hyperbolic scalar and vector potential by means of parametric Nikiforov–Uvarov method. Ikot et al 68 studied Schrodinger equation with screen Kratzer potential in the presence of external magnetic and AB flux field using factorisation method. The eigenvalue and the eigenfunction of the system were presented in a close form while magnetisation and magnetic susceptibility were evaluated at zero and finite temperatures as well as thermodynamic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Likewise, some oscillator potentials that are closely related to this potential have already been studied a few years ago. [17,18] Recently, bound-state solutions have been obtained for the Kratzer potential, [19,20] Morse, Pöschl-Teller potential, [21] Deng-Fan-Eckart potential, [22] and Aharanov-Bohm magnetic field, [18,19,23] and some of them have been investigated for information theoretic measures and the thermal properties of some molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic functions such as; free energy, entropy, internal energy, and specific heat capacity functions can be obtained from the partition function (31) as follows [20].…”
Section: Thermal Properties Of Generalized Trigonometric Pöschl-tellementioning
confidence: 99%
“…The exact analytical solutions of the Schrödinger equation with some of these potentials are only possible for = 0. For = 0 states, one has to employ some approximations, such as the Pekeris approximation [17,18], to deal with the orbit centrifugal term or solve numerically [19,20]. Several mathematical approaches have been developed to solve differential equations arising from these considerations.…”
Section: Introductionmentioning
confidence: 99%